Transcending subjectivity: artistic and creative development in university students. - Fernández-Company, José Fernando; Gamella-González, David José; García-Rodríguez, María (EPSIR (European Public & Social Innovation Review),, 2025)
This study addresses the gap in literature by examining how anticipatory methodologies impact college students' self-assessment of art subjects during their Teacher Education Degree training. Methodology: Sixty-eight third-year undergraduate students in Primary Education participated, predominantly women (82,5%), aged 20 to 28 years (M= 22,18; SD= 1,95). Using quantitative methods, the research evaluated how anticipatory teaching approaches predict positive learning outcomes and prevent student demotivation in art education. Results: Findings revealed significant enhancements in students' artistic and creative skills through these methodologies, with younger participants showing notable advancements. Discussions: Discussions highlighted the importance of cultivating positive student self-perception, robust teacher support, diverse definitions of academic success, and implementing varied educational models to optimize learning experiences. Ultimately, integrating anticipatory methodologies into art education not only enriches artistic and creative abilities but also fosters holistic learning. Conclusions: The study advocates for social inclusion and cultural heritage preservation to sustain and enhance the role of artistic education in providing quality and comprehensive learning environments. These insights contribute to advancing educational practices that empower students and promote a broader understanding of academic achievement in the context of art and creativity.
Trascendiendo la subjetividad: desarrollo artístico y creativo en estudiantes universitarios
Introducción: Este estudio aborda el vacío existente en la literatura examinando cómo las metodologías anticipatorias influyen en la autoevaluación de los estudiantes universitarios de asignaturas artísticas durante su formación en el Grado de Magisterio.Metodología: Participaron 68 estudiantes universitarios de tercer curso de Grado en Educación Primaria, predominantemente mujeres (82,5%), con edades comprendidas entre los 20 y los 28 años (M= 22,18;DT= 1,95). Utilizando métodos cuantitativos, la investigación evaluó cómo los enfoques de enseñanza anticipatoria predicen resultados de aprendizaje positivos y previenen la desmotivación de los estudiantes en educación artística.Resultados: Los resultados revelaron mejoras significativas en las habilidades artísticas y creativas de los estudiantes a través de estas metodologías, y los participantes más jóvenes mostraron avances notables.Discusión: Los debates destacaron la importancia de cultivar una autopercepción positiva de los estudiantes, un sólido apoyo del profesorado, diversas definiciones de éxito académico y la aplicación de modelos educativos variados para optimizar las experiencias de aprendizaje. En última instancia, la integración de metodologías anticipatorias en la educación artística no sólo enriquece las capacidades artísticas y creativas, sino que también fomenta el aprendizaje holístico.Conclusiones: El estudio aboga por la inclusión social y la preservación del patrimonio cultural para sostener y potenciar el papel de la educación artística en la provisión de entornos de aprendizaje integrales y de calidad. Estas reflexiones contribuyen al avance de las prácticas educativas que capacitan a los estudiantes y promueven una comprensión más amplia del rendimiento académico en el contexto del arte y la creatividad.
Keywords: Scopus; anticipatory methodologies; art education; teacher training; student self-assessment; creative skills development; gender differences; academic success perspectives; holistic learning integration; metodologías anticipatorias; educación artística; formación del profesorado; autoevaluación del alumno;; desarrollo de habilidades creativas; diferencias de género; perspectivas de éxito académico; integración holística del aprendizaje